2016
DOI: 10.1159/000453078
|View full text |Cite
|
Sign up to set email alerts
|

Simple Cysts in Donor Kidney Contribute to Reduced Allograft Function

Abstract: Background: Simple renal cysts may be an early marker of renal disease. We investigated whether simple cysts in donor kidney are associated with the decline of allograft function in living donor kidney transplantation. Methods: We retrospectively reviewed records of donors and recipients from 716 living donor kidney transplants performed between April 2007 and April 2015 in our hospital. Ninety-one donors with renal cysts and 64 recipients with cysts in donor kidney were noted. We compared these 64 cases to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Our finding that donors with retained renal cysts had slightly lower eGFR at baseline than donors without cysts (median 94 vs 98 mL/min/1.73 m 2 , P < .01) is consistent with a recent study of 716 living donor transplants performed in China, which found that donors with renal cysts (N = 91) had lower predonation eGFR (100 vs 106 mL/min/1.73 m 2 ) 40 . While donors with retained cysts had a lower average eGFR than those without cysts at baseline (difference = −5.6, P < .001) and throughout the follow‐up period, this association was confounded by donor age at donation: When adjusting for age alone, the association between retained cysts and eGFR was not significant ( P = .4).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that donors with retained renal cysts had slightly lower eGFR at baseline than donors without cysts (median 94 vs 98 mL/min/1.73 m 2 , P < .01) is consistent with a recent study of 716 living donor transplants performed in China, which found that donors with renal cysts (N = 91) had lower predonation eGFR (100 vs 106 mL/min/1.73 m 2 ) 40 . While donors with retained cysts had a lower average eGFR than those without cysts at baseline (difference = −5.6, P < .001) and throughout the follow‐up period, this association was confounded by donor age at donation: When adjusting for age alone, the association between retained cysts and eGFR was not significant ( P = .4).…”
Section: Discussionsupporting
confidence: 92%
“…In adult patients a correlation has been shown between simple cysts and hypertension and renal dysfunction . Grafts with simple cysts have been shown to have increased allograft dysfunction . Until now, no reports have linked simple cysts with renal dysfunction in children.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Grafts with simple cysts have been shown to have increased allograft dysfunction. 20 Until now, no reports have linked simple cysts with renal dysfunction in children. In the present study, however, 22% of the renal cyst patients had eGFR <90 mL/min/1.73 m 2 , and two patients had hypertension that was unrelated to any other cause.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of simple renal cysts in donor kidney is also associated with decline in allograft function, as these cysts represent an early marker of renal disease. Data show that the presence of simple cysts in donor kidney influences early and long‐term allograft function, but not 5‐year allograft survival . There is a lack of pediatric data, and also of analysis, between LDs with simple cyst vs SCD.…”
Section: Other Non‐standard Criteria Donorsmentioning
confidence: 99%
“…Data show that the presence of simple cysts in donor kidney influences early and long-term allograft function, but not 5-year allograft survival. 63 There is a lack of pediatric data, and also of analysis, between LDs with simple cyst vs SCD. or shunt operation has been performed.…”
Section: Other Non -S Tandard Criteria Donor Smentioning
confidence: 99%